Estudo numérico da transferência de calor na alvenaria com blocos cerâmicos em situação de incêndio - Quispe, Alana Paula da Costa (2022)
As the availability of computational resources grows, the use of numerical models to solve thermal problems has been widespread and recommended. In problems related to the performance of buildings in a fire situation, the numerical modeling can complement experimental tests, allowing the analysis and evaluation of a physical system with alternative solutions and more assertive decisions. Thus, the purpose of the present research was to numerically analyze the heat transfer in masonry prisms and wallets with structural ceramic blocks in fire situation using the thermal insulation criterion of the standard NBR 16965:2021. All models were developed using Abaqus software. The fire was simulated using the ISO 834:1999 standardized curve. The research was divided into two stages that resulted in two scientific articles. The first article presents a comparative study of different modeling strategies: homogenized models, micromodeling considering constant thermophysical properties and with thermal properties varying with temperature. In the homogenized model, a program was developed to calculate the homogenized properties of different masonry configurations. The second article evaluated the heat transfer in wallets considering the influence of the coating and the variation of thermal properties. Initially, the wallet model was validated with an experimental test, then other wallets with different block geometries were modeled. In all models, it was found that the configuration constituted by the block with the highest percentage of leaks in the block presented a better thermal behavior. The use of the coating considerably increases the fire resistance time. The consideration of the variation of properties as a function of temperature allows more accurate results, allowing the model to consider some physical phenomena that occur at high temperatures, such as the process of evaporation of moisture around 100 °C. The moisture content of the masonry constituent materials directly influences the temperature distribution on the face not exposed to fire. For quick and less in-depth analyses, it is recommended to use homogenized models or detailed models with constant properties, in which the processing time is shorter, however with more conservative and less accurate results. The use of detailed micromodeling with properties varying with temperature allows simulating problems with greater precision and analyzing specific regions. For all cases, it was observed that the highest temperatures were concentrated in the mortar joints, however it is important to emphasize that the behavior of the materials depends directly on the thermophysical properties, so each material can have a better thermal performance when it has low thermal conductivity and high specific heat.